Palindromic rheumatism: a unique and enigmatic entity with a complex relationship with rheumatoid arthritis. (3rd April 2021) - Sanmartí, Raimon; Haro, Isabel; Cañete, Juan D
ABSTRACT: Introduction: Palindromic rheumatism (PR) is a form of relapsing/remitting arthritis that may evolve to chronic rheumatic disease, mainly rheumatoid arthritis (RA). The exact nature of PR is unclear, as it may be considered a disease in itself, an abortive form of RA or just a pre-RA stage. Areas covered: The authors review the most relevant epidemiological and clinical aspects of PR, especially the pathogenetic role of autoimmunity in PR, with most patients having a characteristic autoantibody profile similar to that observed in RA. The role of autoinflammation is also discussed. A literature review on the rate of RA progression and its prognostic factors was analyzed. Data on the efficacy of drug therapies used to treat PR are presented. PubMed was searched using the terms 'palindromic rheumatism' OR 'palindromic arthritis'. Expert opinion: PR is a disease entity with a close but unclear relationship with RA. In PR there is an unmet need, which is to clarify the clinical spectrum and elucidate the risk factors for evolution to RA. The role of autoimmunity and the autoinflammatory component should be investigated. Since most patients evolve to RA, PR may display a unique therapeutic opportunity to avoid this evolution.